1991
DOI: 10.1254/jjp.55.51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Panax ginseng on age-related changes in the spontaneous motor activity and dopaminergic nervous system in the rat.

Abstract: -Effectsof Panax ginseng on the spontaneous motor activity and central dopaminergic systems in old rats were investigated and compared with those in young rats. Oral intake of a 1.8% water extract of Panax ginseng for four weeks produced an increase in spontaneous motor activity during the dark period in old rats, while it caused a decrease in the activity in young rats. After the intake of ginseng extract for five weeks, it caused a significantly low dopamine utilization in the daytime in the striatum of old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Furthermore, it has been reported that ginseng extract had anti-fatigue effects in mice (19) and increased spontaneous motor activity during the dark period in aged rats (20). Therefore, these findings suggest that amelioration of performance decline in Ischemia + ginseng and Aged + ginseng rats might be attributed to elevated motor activity induced by ginseng, which seems to have both peripheral and central effects.…”
Section: Effects Of Red Ginseng On the Central Nervous Systemmentioning
confidence: 74%
“…Furthermore, it has been reported that ginseng extract had anti-fatigue effects in mice (19) and increased spontaneous motor activity during the dark period in aged rats (20). Therefore, these findings suggest that amelioration of performance decline in Ischemia + ginseng and Aged + ginseng rats might be attributed to elevated motor activity induced by ginseng, which seems to have both peripheral and central effects.…”
Section: Effects Of Red Ginseng On the Central Nervous Systemmentioning
confidence: 74%
“…Anxiolytic effects have also been demonstrated in mice and maze models. Ginseng and ginsenosides have been shown to positively impact striatal dopaminergic activity and dopamine receptors [175], which could translate to a minimal apomorphine like effect. Ginseng may exert a direct effect on the hypothalamus or pituitary to also suppress prolactin secretion, but these hormonal changes I believe are minor at best because past clinical trials measuring hormonal changes in men did not find significant or consistent increases in prolactin or testosterone [176].…”
Section: Panax Ginseng and Ginsenosides (Korean Red Ginseng And Others)mentioning
confidence: 99%
“…A 1 : 9 (w/v) slurry of powdered American ginseng root and distilled water was extracted in a water bath with agitation for 1 h at 90 -C, a modification of a previous protocol (Watanabe et al, 1991). The extract was cooled for 30 -45 min and then centrifuged at 1200 g for 15 min.…”
Section: Plant Materials and Ginseng Extractsmentioning
confidence: 99%